2008
DOI: 10.1021/cm702359r
|View full text |Cite
|
Sign up to set email alerts
|

Facile Mesophase Control of Periodic Mesoporous Organosilicas under Basic Conditions

Abstract: The mesophase structure of ordered periodic mesoporous organosilicas (PMOs) can be easily adjusted under basic conditions by variation of the sodium hydroxide concentration. PMOs with hexagonal (p6mm, two-dimensional pore system), cubic (Pm3n or Fm3m, three-dimensional cagelike pore system), and disordered hexagonal (MSU-type) symmetry were obtained from 1,2-bis(triethoxysilyl)ethane (BTEE)-derived synthesis gels in the presence of binary surfactant mixtures, [CH 3 (CH 2 ) 15 NMe 3 ] + Br -(C 16 TABr) and [CH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 103 publications
2
24
0
1
Order By: Relevance
“…The H2 hysteresis loop found for OMOs-13 is the characteristic of the cage-like mesopores. The total pore volume of OMOs-13 is 0.73 cm 3 /g, only half of that of OMOs-20 (Table 1), confirming the presence of a large domain of cubic mesostructure according to the previous report that the pore volume of a 2D hexagonal mesophase is twice more than that of a cubic mesophase [35]. Expectably, OMOs-10 and OMOs-8 also display H2 hysteresis loops, implying a cage-like pore structure connected by small windows.…”
Section: Characterization Of Omos-nsupporting
confidence: 79%
See 1 more Smart Citation
“…The H2 hysteresis loop found for OMOs-13 is the characteristic of the cage-like mesopores. The total pore volume of OMOs-13 is 0.73 cm 3 /g, only half of that of OMOs-20 (Table 1), confirming the presence of a large domain of cubic mesostructure according to the previous report that the pore volume of a 2D hexagonal mesophase is twice more than that of a cubic mesophase [35]. Expectably, OMOs-10 and OMOs-8 also display H2 hysteresis loops, implying a cage-like pore structure connected by small windows.…”
Section: Characterization Of Omos-nsupporting
confidence: 79%
“…doi:10.1016/j.jcis.2010.02.020 lamellar, bicontinuous cubic Ia3d, 2D hexagonal p6mm, 3D hexagonal p6 3 /mmc, and cubic Pm3m symmetry using different gemini surfactants as structure-directing agents under basic conditions [34]. Liang et al synthesized a series mesoporous organosilicas with cubic and hexagonal symmetry under basic condition and revealed the effect of sodium hydroxide on the mesoporous organosilicas mesophase structure based on the charge-matching mechanism [35][36][37][38]. Kipkemboi et al found that the length of the EO blocks of polymer templates is essential for establishing a mesoporous structure and only long EO chains can lead to a cubic structure [39].…”
Section: Introductionmentioning
confidence: 99%
“…The PXRD pattern of Me‐HSMSCSNs shows a series of well‐resolved diffraction peaks in the 2 θ range of 1.4–4.5°, which can be indexed as the (210), (211), (321), (400), (420), and (422) reflections of the cubic Pm true3 n space group, arising from the PMO core structure (cf. Me‐PMO, Figure S18 of the Supporting Information) . The (100) plane indicated by the peak/shoulder at 2 θ =1.495° may represent a distorted hexagonal p 6 mm symmetry of the shell layer with large pore size (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 9 The mesoporous structure of MC is also evidenced by the nitrogen adsorption-desorption isotherm, as shown in Fig. It is clearly seen that the MC products consist of a large amount of NPs.…”
mentioning
confidence: 88%